Role Of Dinacharya in the Prevention of Urdhwajatrugata Vikaras : A Review Article - M, Ramya; Katti, Anand (International Research Journal of Ayurveda & Yoga, 2021)
Tridosha siddhanta is one of the fundamental principles of Ayurveda. Vata, pitta and kapha are the driving forces for the human physiology. Normalcy among them is health and abnormally leads to disease. These doshas tend to vary in quantity and quality by daily activities, food and many external causes. Ayurveda samhitas advocate dinacharya, which are set of daily regimen practices to keep these doshas in a state of normalcy. Therefore, these regimens are preventive management also health promotive in nature. Shalakya tantra is that branch of Ayurveda which addresses diseases pertaining to Eye, Ear, Nose, Throat, oral cavity, teeth, headaches and skin disease pertaining to scalp. This article segregates and analysis the dinacharya (daily regimen) that specifically have nexus with Urdhwajatrugata vikara.